UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI KELILING DAN LUAS BANGUN DATAR MELALUI PEMBELAJARAN KONTEKSTUAL DI KELAS III SDN 43 BILAH HULU - Lentarina Siregar (CV. ADIBA AISHA AMIRA, 2023)
This research aims to (1) find out whether there is an increase in students' learning achievement in mathematics through contextual learning in class III at SDN 43 Bilah Hulu on the subject of perimeter and area of flat shapes (2) find out what students' attitudes towards contextual learning are in class III at SDN 43 Bilah Hulu. on Roving material. This research is Classroom Action Research. The subjects who gave the action in this research were the class teachers in mathematics lessons, while the class III students at SDN 43 Bilah Hulu, consisting of 31 students, were the research subjects who received the action. Researchers as observers are tasked with planning, collecting data, analyzing data and drawing conclusions. The research object studied was mathematics learning in an effort to increase student learning achievement through contextual learning. Based on the research results, it can be concluded that student learning achievement in calculating the perimeter and area of the perimeter and area of flat shapes by applying contextual learning has increased in class III at SDN 43 Bilah Hulu. The average for the first cycle class increased from the initial test by 3.06%, while the percentage of students' classical abilities increased by 32.26%. The class average in cycle II increased from cycle I by 19.36%, while classical ability increased by 34.21%. Students' attitudes towards receiving learning using contextual learning were very positive because in cycle I student activity in participating in contextual learning was 56.14% and increased in cycle II to 83.33%. Meanwhile, student observations in cycle I were 62.50%, increasing in cycle II to 85.42%.